A Qualitative Study Of The Perception And Experience Of Childbearing Age Couples About Contraception In Wirogunan Sub-District, Mergangsan District, Yogyakarta City - Susiana Sariyati; Dyah Pradnya Paramita (Alma Ata University Press, 2020)
The use of contraceptives is one of the factors that directly affect fertility. Couples of childbearing age (PUS) decisions using contraceptives are influenced by various factors such as demographic, social, economic, legal, political, and environmental conditions. Information on the level of contraceptive use is important to measure the success of the Population, Family Planning, and Family Development Program. Through this strategic goal, the BKKBN seeks to increase the use of modern contraception to control birth rates. The purpose of this study is to determine the perception and experience of PUS regarding the use of modern contraception. The research method used is descriptive qualitative. The subjects in this study were PUS who used traditional family planning, village midwives, cadres in Wirogunan, Mergangsan, Yogyakarta City. Primary data collection on the informant is done by in-depth interviews with PUS using traditional family planning. The results of this study indicate that the PUS perception of the majority of respondents said that modern contraception will fail if it uses an IUD. While most respondents' experiences convey a lot of side effects. This study concludes that PUS perception about modern contraception is a negative perception of fear of failure and experiencing side effects. It is recommended that socialization on modern contraceptive methods by experts from midwives or doctors be trusted by the public regularly